ANALISIS BIAYA TRANSAKSI USAHATANI PADI DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Ilma Satriana Dewi; Septina Elida; Dini Amalia Putri (DINAMIKA PERTANIAN, 2019)
The rice plant is one of the agricultural products and is a major food for almost all the people of Indonesia. Farming capital is the production cost that will be spent by farmers during the production process. However, in addition to production costs, there are other costs unwittingly incurred by farmers which are also related to their farming activities. These costs are known as transaction costs. The purpose of this study was to analyze components and total transaction costs and the effect of transaction costs on economic efficiency of rice farming. The data were analyzed using descriptive qualitative and quantitative descriptive approaches. Transaction cost was analyzed by using transaction cost analysis. The results showed that the components of rice farming transaction costs along with their ratio consisting of information costs (0,05), negotiation costs (0,02), coordination costs (0,79), implementation costs (0,03), risk costs (0,08) and transportation costs (0,03). The effect of transaction costs on revenue was seen from the ratio value which wais equal to 0,009. Meanwhile, the factors that significantly affect transaction costs were farming experience and subscription.